Hand-Rearing Technique of Tropical Deer from Birth to Weaning A - Gono Semiadi (Media Konservasi, 1997)
A technique in hand-rearing of tropical deer from birth to weaning age was developed using 52 sambar (Cervus unicolor) fawns. Fawns were best snatched between 24 to 48 hrs after birth. A milk powder specially made for daii calves was the best compared to the homogenized commercial milk. Suitable length of the artificial teat was between 3 to 4.2 cm, with the slit length of 3 mm. The main problems during the rearing time were the refusal in taking the first artificial mik diarrhoea, bloat and suckling the penis, button or anal areas. Giving moist dirts of 112 teaspoon once a day after the feeding would reduce the incident of bloating or diarrhoea.